The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1136/jnnp.2008.158196
|View full text |Cite
|
Sign up to set email alerts
|

S-100B and neuron specific enolase are poor outcome predictors in severe traumatic brain injury treated by an intracranial pressure targeted therapy

Abstract: Objective: To prospectively study S-100B and neuron specific enolase (NSE) levels in subjects treated for severe head injury (sTBI), and investigate the prognostic value of these biomarkers. Methods: Subjects included in a prospective double blind randomised study for sTBI. Inclusion criteria: Glasgow Coma Score (GCS) (8, age 15-70 years, first recorded cerebral perfusion pressure of .10 mm Hg and arrival ,24 h after trauma. Subjects were treated with an intracranial pressure (ICP) targeted therapy. Blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 41 publications
(43 reference statements)
4
34
1
1
Order By: Relevance
“…When compared to NSE, S100B has a higher overall predictive power, in accordance with other groups analyzing and comparing both biomarkers [59–61], where the predictive capability of NSE was found limited in the presence of S100B in multivariate outcome models [39, 62]. An explanation is, again, the notable covariance between serum S100B and NSE, which has been shown to be 0.50–0.78 (correlation coefficient) in previous studies [39, 58, 63, 64], similar to ours of 0.67. However, in our study this correlation decreases over time, highlighting the need for more granular temporal considerations when assessing biomarkers [65].…”
Section: Discussionsupporting
confidence: 85%
“…When compared to NSE, S100B has a higher overall predictive power, in accordance with other groups analyzing and comparing both biomarkers [59–61], where the predictive capability of NSE was found limited in the presence of S100B in multivariate outcome models [39, 62]. An explanation is, again, the notable covariance between serum S100B and NSE, which has been shown to be 0.50–0.78 (correlation coefficient) in previous studies [39, 58, 63, 64], similar to ours of 0.67. However, in our study this correlation decreases over time, highlighting the need for more granular temporal considerations when assessing biomarkers [65].…”
Section: Discussionsupporting
confidence: 85%
“…There was no statistically significant difference between the control and prostacyclin groups in regard to age (un-paired Student's t test), gender (χ 2 test), GCS, GOS at 3, 6, and 12 months, Marshall, Rotterdam, and Morris-Marshall classifications (Wilcoxon rank-sum test). As previously reported, there was no difference in ISS, Sum score a +1 a Add plus 1 to make the grading numerically consistent with the grading of the motor score of the GCS and with the Marshall CT classification APACHII, S-100B, NSE, APOE, and microdialysis showed no significant differences in intracerebral lactat/pyruvate ratio or glucose between the placebo and prostacyclin group [31][32][33][34]. Thus, for further analysis of the results, the enrolled subjects are treated as one group.…”
Section: Resultsmentioning
confidence: 59%
“…Previous studies have demonstrated that serum NSE levels often reflect the extent of brain injury, and that increased serum NSE within the first three days after cardiac arrest is associated with poor outcome [3335]. However, serum NSE levels after brain injury displayed a gradual decline over time [36], which indicates that NSE collected from patients in the late phase of brain injury cannot be used as a prognostic factor to predict the outcome of patients with UWS.…”
Section: Discussionmentioning
confidence: 99%